Accepting Multipurpose “Smart” Identity Cards in a Developing Country - Heng, Paul Ping Yeow; Loo, Wee Hong; Chong, Siong Choy (Taylor & Francis Group, 2007)
Accepting multipurpose "smart" identity cards in a developing country